2020
DOI: 10.3390/v12080831
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterizations and Molecular Evolution of VP7 Gene in Human Group A Rotavirus G1

Abstract: Rotavirus group A (RVA) G1 is one leading genotype circulating in humans worldwide, and related molecular information from a global perspective is still limited. Here, we present a comprehensive description of the genetic characterizations and molecular evolution of the RVA G1 VP7 gene. Our results show that RVA G1 can be divided into two lineages and multiple sub-lineages with a relatively high genetic diversity. Vaccine strains are phylogenetic, closer to lineage I. The evolutionary rate of the RVA G1 VP7 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A previously described algorithm was used to demonstrate the accumulation pattern of amino acid substitutions of the norovirus GI RdRp gene [ 29 , 30 ]. In brief, the number of pairwise amino acid differences was calculated by MEGA 7.0.26 and averaged.…”
Section: Methodsmentioning
confidence: 99%
“…A previously described algorithm was used to demonstrate the accumulation pattern of amino acid substitutions of the norovirus GI RdRp gene [ 29 , 30 ]. In brief, the number of pairwise amino acid differences was calculated by MEGA 7.0.26 and averaged.…”
Section: Methodsmentioning
confidence: 99%
“…Mutation patterns differed depending on the year of detection. Mutations N94S, S123N, M217T, and K291R have been reported in strains isolated from other countries ( Novikova et al, 2020 ; Zhou et al, 2020 ), suggesting that these substitutions have already been reported in recent G1 epidemic strains. Additionally, in this study, the VP7 gene harbored the L148F mutation in 2012 and 2014, the D100E mutation in 2015 and 2019, the T242M mutation in the G1P[8] (DS-1) strain in 2012–2015, and the N147D mutation in the G1P[8]-E2 strain in 2015 and 2018.…”
Section: Discussionmentioning
confidence: 82%